Chitosan Grafted With β-Cyclodextrin: Synthesis, Characterization, Antimicrobial Activity, and Role as Absorbefacient and Solubilizer - Ding, Wen-Ya; Zheng, Si-Di; Qin, Yue; Yu, Fei; Bai, Jing-Wen; Cui, Wen-Qiang; Yu, Tao; Chen, Xing-Ru; Bello-Onaghise, God'spower; Li, Yan-Hua (Frontiers in Chemistry, 2019)
We synthesized chitosan grafted with β-cyclodextrin (CD-g-CS) from mono-6-deoxy-6-(p-toluenesulfonyl)-β-cyclodextrin and chitosan. Two different amounts of immobilized β-cyclodextrin (β-CD) on CD-g-CS (QCD: 0.643×103 and 0.6×102 μmol/g) were investigated. The results showed that the amino contents of CD-g-CS with QCD=0.643×103 and 0.6×102 μmol/g were 6.34% ± 0.072% and 9.41% ± 0.055%, respectively. Agar diffusion bioassay revealed that CD-g-CS (QCD = 0.6×102 μmol/g) was more active against Staphylococcus xylosus and Escherichia coli than CD-g-CS (QCD = 0.643×103). Cell membrane integrity tests and scanning electron microscopy observation revealed that the antimicrobial activity of CD-g-CS was attributed to membrane disruption and cell lysis. Uptake tests showed that CD-g-CS promoted the uptake of doxorubicin hydrochloride by S. xylosus, particularly for CD-g-CS with QCD=0.6×102 μmol/g, and the effect was concentration dependent. CD-g-CS (QCD = 0.6×102 and 0.643×103 μmol/g) also improved the aqueous solubilities of sulfadiazine, sulfamonomethoxine and sulfamethoxazole. These findings provide a clear understanding of CD-g-CS and are of great importance for reducing the dosage of antibiotics and antibiotic residues in animal-derived foods. The results also provide a reliable, direct and scientific theoretical basis for its wide application in the livestock industry.